Promoting responsible science and CBRN security through codes of conduct and education - Tatyana Novossiolova; Maurizio Martellini (Elsevier, 2019)
The paper examines the utility of codes of conduct for promoting responsible science and chemical, biological, radiological, and nuclear (CBRN) security education. It reviews the growing international consensus on the need for developing codes of conduct as a way of engaging scientists with the broader social, ethical, and legal implications of their work and examines the ongoing efforts to develop and promulgate such codes. The paper argues that the effectiveness of codes of conduct requires sustained and tailored effort in promoting education and awareness of security issues among scientists.